How learning happens : seminal works in educational psychology and what they mean in practice - Kirschner, Paul A.; Hendrick, Carl (2020)
"How Learning Happens introduces 28 giants of educational research and their findings on how we learn and what we need to learn effectively, efficiently and enjoyably. Many of these works have inspired researchers and teachers all around the world and have left a mark on how we teach today"--
Includes bibliographical references and index.
Keywords: Learning, Psychology of; Educational psychology; Effective teaching